2018
DOI: 10.1177/1525740118783040
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Choral Singing Intervention on Speech Characteristics in Individuals With Parkinson’s Disease: An Exploratory Study

Abstract: The purpose of this exploratory study was to examine speech characteristics in individuals with Parkinson’s disease (PD) before and after participation in an 11-week choral singing intervention. Speech characteristics were analyzed using an acoustic measure of vowel space area (VSA) and a standardized speech intelligibility metric. Participants included five males and five females with PD. VSA was derived for the corner vowels (/i/, /u/, /æ/ /α/) produced during a sentence-level task. VSA was expressed as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…Sample sizes ranged from 10 (Yinger and Lapointe 2012, Higgins et al . 2018, Elefant et al . 2012) to 75 (Tamplin et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample sizes ranged from 10 (Yinger and Lapointe 2012, Higgins et al . 2018, Elefant et al . 2012) to 75 (Tamplin et al .…”
Section: Resultsmentioning
confidence: 99%
“…2016), two used a trained vocal performer/singing teacher (Higgins et al . 2018, Evans et al . 2012), two employed professional choir directors (i.e., Zumbansen et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, choral singing therapy is based on the principle of overlapping areas of bi-hemispheric cortical activation to treat motor speech abnormalities associated with neurological disorders like PD. 33 The patient's cognitive and functional skills, awareness of her voice quality, compliance with medical advice, and family support may be considered positive prognosticating factors for the success of the telerehabilitation program. There was no report of problems with the internet and audiovisual clarity in this case, given the usual bandwidth commonly available from home wi-fi, which usually averages 18.6 megabits per second (Mbps) in the Philippines.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also highlight the increased opportunities for socialization, support, and integration of more client-driven goals into the activities, and how the practice in more naturalistic contexts as well as the social aspects of group intervention can facilitate better generalization of treatment targets and potentially also motor learning. More specifically, researchers have found that well-structured group therapy can provide similar quantitative benefits to individual therapy in primary intervention for speech deficits, as reflected by significant improvements in measures such as vocal intensity [31][32][33][34][35], maximum phonation time (MPT) [32,33,35,36] and intelligibility [37,38]. In addition, studies have demonstrated that group therapy can be effective in maintaining the gains resulting from intensive individual therapy [33,39].…”
Section: Introductionmentioning
confidence: 99%